The Wroblewski Library History: Case of the Purchase of the Plater’s Pustynia Estate Book Collection - Narbutienė, Daiva (Knygotyra, 2019)
The founder of the Wroblewski Library of the Lithuanian Academy of Sciences, Tadeusz Stanisław Wróblewski (1858–1925), began to enrich the library of his parents, which he inherited in 1891, through his acquisitions of books, manuscripts, periodicals, collections of iconographic documents, and other valuables. One of such book collections, offered to him for sale in 1907, was from the Pustynia Estate located near the town of Kraslava, then part of the Vitebsk Province (Kraslava now is a municipality center in the Republic of Latvia, situated not far from Daugavpils and near the border with the Russian Federation). This collection belonged to Count Henryk de Broel-Plater (1868–after 1926). Having studied its catalogue, Wroblewski purchased from the count his entire collection (over 6000 volumes) on October 30, 1907, for 2.5 thousand roubles. However, Plater had hid several hundred of his most valuable books, which he later offered to Hieronym Wilder’s antique bookshop in Warsaw. Wroblewski had to exercise a considerable effort to reclaim the books he rightly owned. Based both on archival materials kept in the Wroblewski Library of LAS and on evidence collected about publications carrying the Pustynia Estate provenance mark (350 copies have been identified so far), the article discusses the circumstances of the purchase of Plater’s book collection and overviews its content and development. The Pustynia estate library was rather universal by its content and contained extremely valuable editions. Wroblewski purchased from the count, among other rarities, Joannes Radvanus’s Radivilias (Vilnae, Metropoli Litvanorum: ex officina Ioannis Kartzani, 1592), a Latin biography by the Lutheran pastor Paul Oderborn Ioannis Basilidis magni Moscoviae ducis vita (Witebergae: excudebat haeredes Ioannis Cratonis, 1585), and a treatise on the differences between the Catholic and the Orthodox faiths by the Kraków canon Jan Sakran, Elucidarius errorum ritus Ruthenici (Cracoviae: typis Joannis Haller, post V 1501). There are no more copies of these and several other Plater’ s books in Lithuania.
Keywords: private libraries; adeusz Stanisław Wróblewski; Henryk de Broel-Plater; Pustynia Estate; book heritage; the Wroblewski Library of the Lithuanian Academy of Sciences